The Practice of Scottish Urologists in the Assessment and Management of Fracture Risk in the Ageing Male being Treated for Prostate Cancer - Wee Sing Ngu; Derek J. Byrne (The Scientific World Journal)
The aim of this study was to ascertain the practice of urologists in Scotland in the assessment and prevention of fracture risk in males starting castration-type therapy for prostate cancer. A questionnaire survey was sent to all practicing consultant urologists in Scotland. A majority of urologists, 25 (64.1%), did not consider the state of their patients' bone mineral density (BMD) before commencing castration-type therapy. The rest used various methods to assess BMD, including clinical impression alone, plain bone radiographs, and dual-energy X-ray absorptiometry (DEXA). Various methods were used in the prophylaxis and treatment of osteoporosis, including avoidance of castration type therapy and the use of bisphosphonates and bicalutamide along with castration-type therapy. This study has shown that there is no consensus as to the assessment and management of fracture risk in patients with prostate cancer commencing or on established castration-type therapy. The situation needs to be addressed with some consensus guidance.